Ethnoveterinary Practice May be an Alternative to Antibiotics in Dairy Cattle - Shridhar, Dr. N. B. (International Journal of Environment, Agriculture and Biotechnology, 2024)
Ethnoveterinary practices in India have their origins in ancient times, characterized by the transmission of indigenous knowledge, beliefs, and skills related to the diagnosis, treatment, and management of diseases in both animals and humans. These practices, preserved and refined over generations, have evolved into cost-effective alternatives to conventional medicine, particularly benefiting small-scale farmers. In contemporary veterinary medicine, the integration of ethnoveterinary practices presents a viable strategy for reducing the overreliance on antibiotics. These traditional methods not only support growth and productivity in livestock but also offer effective solutions for the prevention and treatment of common animal diseases. The adoption of such practices holds significant potential in addressing the escalating threat of multidrug-resistant pathogens. Many such plant based remedies are there in veterinary practice that can be used as a preliminary alternative to antibiotic use in primary health care of the animals. However, to fully harness the benefits of ethnoveterinary medicine, further research is needed to validate these practices, including studies on dosage, duration, pharmacokinetics, pharmacodynamics, and toxicity patterns including residual effects as they also do contain potent active principles.